Associations Between Perceived Fruit and Vegetable Intake and Nutrition Messaging: Results from a Population-Based Survey Among US Adults. (29th May 2020) - Dumas, Brianna; Lee, Seung Hee; Park, Sohyun; Harris, Diane; Thomas, Christopher
Abstract: Objectives: Fruit and vegetable (FV) intake among US adults is low, and one strategy to increase FV intake is through tailored messaging. We examined associations between perceived FV intake and nutrition messaging using 2018 national panel data of US adults. Methods: The outcome variable—perceived FV intake—was determined by one question: "In a usual week, do you feel that you eat as much FV as you need?" Response options were "Yes, I definitely do; Yes, I think so; I'm not sure; No, I don't think so; No, I definitely don't." Three explanatory variables were: ' More children & adults should eat the recommended daily amount of vegetables…fewer than 1 in 10 do .' (OneinTen); ' States & communities can help people consume more FV… in the places…live, work, learn & play.' (LivePlay); 'Adults should fill half their plate with FV at every meal' (HalfFV ). For each message, respondents were asked to indicate agree/neither/disagree with the 3 response statements: ' This message was easy to understand .' (Easy to Understand); 'This message was convincing.' (Convincing); and 'I learned something new from this message' (Learned Something New). Three multinomial logistic regression models were fit to calculate adjusted odds ratios (aOR) controlled for sociodemographic variables. Results: Overall, 37.4% of adults perceived eating enough FV, 13.8% were unsure, and 48.8% perceived not eating enough FV. There was highest agreeance that all messages were easy to understand (77.9%–82.5%) across all strata. Across all strata, LivePlay and OneinTen showed the largest variation in agreeance for learned something new (25.5%–60.3%). Those who perceived not eating enough FV were less likely to report learning something new from LivePlay (aOR = 0.7), and less likely to find HalfFV convincing (aOR = 0.6). When compared to those who perceived eating enough FV, those who were unsure were less likely to find all messages easy to understand and convincing, and less likely to report learning something new from LivePlay (aOR = 0.4) and HalfFV (aOR = 0.6). Conclusions: Our results suggest that there is a future opportunity for tailored communication efforts, especially for those who perceived not eating enough FV, and those who are unsure if they eat enough FV. Funding Sources: Author's time from their institutions.